Pengaruh Kualitas Sumber Daya Manusia, Pemanfaatan Teknologi Informasi dan Pengendalian Intern Terhadap Keandalan Pelaporan Keuangan Pemerintah Nagari Di Kabupaten Padang Pariaman - Dewi Septiani Sukma; Rasyidah Mustika; Eliyanora Eliyanora (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2023)
This study aims to determine the effect of the quality of human resources, the use of information technology and internal control on the reliability of the financial reporting of the nagari government in Padang Pariaman Regency. This research is a quantitative research. Methods of data collection by using a questionnaire that was distributed directly. The population of this research is all nagari governments in Padang Pariaman Regency. The research sample amounted to 51 people. The data analysis used is multiple linear regression analysis using SPSS version 25 program. The results showed that the quality of human resources had no positive effect on the reliability of the nagari government's financial reporting, the use of information technology had a positive effect on the reliability of the nagari government's financial reporting, and internal control had a positive effect on the reliability of the nagari government's financial reporting.